2012
DOI: 10.1186/1471-2458-12-264
|View full text |Cite
|
Sign up to set email alerts
|

Illness meanings and experiences for pre-ulcer and ulcer conditions of Buruli ulcer in the Ga-West and Ga-South Municipalities of Ghana

Abstract: BackgroundGhana is a Buruli ulcer (BU) endemic country yet there is paucity of socio-cultural research on BU. Examining distinctive experiences and meanings for pre-ulcers and ulcers of BU may clarify the disease burden, illness experience and local perceptions of causes and spread, and environmental features of BU, which are useful to guide public health programmes and future research. This study aimed to explain local meanings and experiences of BU for persons with pre-ulcers and ulcers in the Ga-West and Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 52 publications
6
27
0
Order By: Relevance
“…In South Africa, off-road motorcycles have been used for timely collection of blood-specimens that give remote clinics access to diagnostic laboratory services [35]. Collaborating with private health practitioners might also be considered as a pragmatic and cost-effective approach to improve access [30,36]. However, this intervention requires supervision and monitoring by the municipal health management team to ensure that drug protocols are followed strictly and wounds are managed properly.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, off-road motorcycles have been used for timely collection of blood-specimens that give remote clinics access to diagnostic laboratory services [35]. Collaborating with private health practitioners might also be considered as a pragmatic and cost-effective approach to improve access [30,36]. However, this intervention requires supervision and monitoring by the municipal health management team to ensure that drug protocols are followed strictly and wounds are managed properly.…”
Section: Discussionmentioning
confidence: 99%
“…The topic guide included four main domains covering knowledge and perceptions about the cause and presentation of scabies, attitudes towards prevention, treatment-seeking behaviours and scabies treatment practices, and knowledge and perceptions about the consequences of scabies in health and life quality. The development of the questionnaire was based on similar studies about NTDs conducted in West Africa 11,12,13,10 . We utilised a mix of both closed and open-questions covering each of the main domains.…”
Section: Interviews' Topic Guide and Questionnaire Developmentmentioning
confidence: 99%
“…Ackumey et al [20,21] investigated perceptions of BU among those afflicted with BU in both the pre-ulcer and ulcer state in West and South Ga municipalities near Accra. They employed an explanatory model interview guide adapted for BU research.…”
Section: Ghanamentioning
confidence: 99%
“…Studies of health care seeking in all three index countries have reported that enabling factors are a major reason for delays in seeking treatment at hospitals and health posts [9,10,16,20,24,41,44,45]. Enabling factors include the seasonal availability and cost of transportation, direct and indirect treatment costs, and opportunity costs in the form of labor loss, especially during peak agricultural seasons.…”
Section: Enabling Factorsmentioning
confidence: 99%